Causales de deserción en equipos de investigación formativa - Gómez-Zermeño, Marcela Georgina; Toscano Miranda, Raúl Emiro (Revista Científica, 2018)
In this article, the results on the difficulties that cause dropout of student’s informative research teams in higher education are presented. The method chosen was qualitative research with a case study, using data collection techniques interviews, document analysis, observation and field notes. Among the findings of the investigation, it was found that: the desertion (disintegration) of a research team triggers serious problems in the studies, students have difficulty research, for example in the search for information, in teamwork, and for example, they have problems of coexistence.